Aging-based molecular classification and score system in ccRCC uncovers distinct prognosis, tumor immunogenicity, and treatment sensitivity - Zhu, Maoshu; Huang, Chaoqun; Wu, Xinhong; Gu, Ying; Hu, Xiaoxu; Ma, Dongna; Zhong, Weimin (Frontiers in Immunology, 2022)
Aging is a complex biological process and is a major risk factor for cancer development. However, the underlying molecular mechanisms and promising biomarkers of aging in clear cell renal cell carcinoma (ccRCC) remain to be elucidated. In this study, we characterized the aging-associated patterns of ccRCC through integrative analyses of multiple datasets with transcriptomics and genomics. In accordance with the transcriptional expression of aging-associated genes, three distinct molecular subtypes (C1, C2 and C3) were identified, which exhibited different clinical outcomes, biological pathway activity, SNP, CNV, tumor microenvironment (TME), tumor immunogenicity, immunotherapeutic response, and sensitivity to chemo drugs (Axitinib, Pazopanib, Sorafenib, and Sunitinib). The TME characterization indicated that the three clusters were highly consistent with known immune patterns: immune-desert (C1), immune-excluded (C2) and immune-inflamed (C3), respectively. Moreover, we also compared the aging-associated cluster with previously reported six immune subtypes IS1 (wound healing), IS2(IFN-γ dominant), IS3 (inflammatory), IS4 (lymphocyte depleted), IS5 (immunologically quiet) and IS6 (TGF-β dominant). We demonstrated that IS3-subtype patients could be categorized into clinically and molecularly different clusters based on these aging-associated genes. Finally, A agingScore system was constructed from the aging associated phenotype signature, which enabled to reliably and independently predict ccRCC prognosis. The high agingScore patients presented more favorable survival outcomes and effective immune responses. We also discovered that in response to anti-cancer drugs, agingScore was highly positive correlated (drug sensitive) with drugs (ABT737) which targeted in cell cycle and apoptosis regulation pathway, negatively correlated (drug resistance) with drugs (Dabrafenib, Gefitinib, PLX-4720 and Afatinib) which targeted oncogenic related pathways, such as EGFR signaling pathway and ERK MAPK signaling pathway. Several small molecular compounds and three therapeutic targets CYP11A1, SAA1, and GRIK4 were determined for low agingScore patients after in silico screening of potential drug targets and compounds from multiple drug datasets. Overall, we systematically explored the clinical features, molecular mechanism, immune features of aging-associated patterns. The agingScore can be served as a promising prognostic factors and responses to immunotherapy, which provides new strategies for the precision treatment of ccRCC.